Physiological adaptability of Salvadora oleoides to sodicity and salinity stress - KUMAR, ASHWANI; MANN, ANITA; LATA, CHARU; KUMAR, ARVIND (The Indian Journal of Agricultural Sciences, 2022)
An experiment was conducted in microplots at ICAR-Central Soil Salinity Research Institute, Karnal, Haryana during 2013–16 to study the adaptive response of Salvadora oleoides, a facultative halophyte under saline, sodic and mixed saline-sodic conditions. S. oleoides was not able to survive at higher sodicity (pH ~ 10.0) and salinity (ECe ~ 35 dS/m) as well as on the mixed sodicity and salinity levels (pH ~ 9.0 along with ECe ~ 10, 15, 20 dS/m). Stress either salinity or sodicity brought reduction in plant height, chlorophyll content and gas exchange attributes, but S. oleoides maintained gaseous exchange at moderate stress level. S. oleoides accumulated 4 fold higher proline under sodic stress and 6 fold under salinity stress. Other osmolytes, TSS and soluble protein decreased with stress intensification to maintain osmotic balance. In comparison to control, sodicity enhanced Na+ and Cl- by 54.57% and 20.33%, while under salinity, Na+ was enhanced by 141.52–256.09% and Cl- by 47.83–115.58% at ECe ~ 15 and 25 dS/m, respectively. Inspite of such higher increase in Na+ and Cl-, S. oleoides retained good amount of mean K+ (1.22%) in leaf tissue. S. oleoides also maintained leaf Na+/K+ below 1.0 under stress condition of pH ~ 9.5 and ECe ~ 15 dS/m. Based on the studied physio-biochemical analysis, Salvadora oleoides exhibited good adaptive potential under moderate salinity and sodicity stress and could be used as a promising salt-tolerant plant species for plantation in salt affected areas.